Characterization of calcium carbonate obtained from oyster and mussel shells and incorporation in polypropylene - Hamester M.R.R. (2012)
There is a high content of calcium carbonate in mussel and oyster shells, which can be used in the formulation of medicine, in construction or as filler in polymer materials. This work has as its main objective to obtain calcium carbonate from mussel and oyster shells and used as filler in polypropylene compared their properties with polypropylene and commercial calcium carbonate composites. The shellfish was milling and heated at 500 °C for 2 hours. The powder obtained from shellfish were characterized by scanning electron microscopy (SEM), X-ray fluorescence, particle size distribution and abrasiveness and compared with commercial CaCO 3 and mixed with polypropylene. The thermal and mechanical properties of polypropylene with CaCO 3 obtained from oyster and mussel shells and with commercial CaCO 3 were analysed. The results showed that CaCO 3 can be obtained from oyster and mussel shell and is technically possible to replace the commercial CaCO 3 for that obtained from the shells of shellfish in polypropylene composites.